Back to the surface – Daylighting urban streams in a Global North–South comparison - Wantzen, Karl M.; Piednoir, Téa; Cao, Yixin; Vazhayil, Alvin M.; Tan, Chaozhong; Kari, Franz Günter; Lagerström, Mirja; Gerner, Nadine V.; Sommerhäuser, Mario M. (Frontiers in Ecology and Evolution, 2022)
Many urban streams have vanished from the surface as a collateral effect of urban growth. Often, these buried streams have been forgotten, and only street names remind us of their existence. Reasons for stream burial include the gain of space for road or house construction or the use of stream water to transport wastewater. Today, restoration efforts to bring back fully canalized streams to the surface and to restore their stream bed (so-called daylighting) are being increasingly integrated into urban blue-green space planning, recognizing the high ecological and social value of urban streams, especially to support resilience against climate change impacts in cities. In this paper, we briefly revise the impacts of stream burial, present a series of case studies of daylighting from Europe (France, Switzerland and Germany), and compare them with case studies from Asia (China, India, Taiwan). We found that high real estate prices, limited buffer riparian zone and resistance by the inhabitants were the greatest obstacles to stream daylighting projects. In contrast, economic gains from separating wastewater from rainwater and revival of cultural linkages with water were the strongest drivers to restore these streams. We then present methods on how to identify buried streams as candidates for daylighting and deliver criteria to select the most promising candidates. Acknowledging that each restoration project requires to be adapted to the local biophysical and local setting, we deliver a preliminary decision support system and a guideline for identifying the best candidate streams for daylighting projects, including the arguments in favor of restoration, the caveats, the social processes of decision-making, and perspectives for the integration of stream daylighting into urban climate change mitigation and adaptation concepts, in a Global North-South comparison.